Pemanfaatan Media Sosial Untuk Penyuluhan Agama Hindu - I Gusti Ngurah Triyana; Ni Ketut Sri Ratmini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Social media is a new phenomenon that colors human life, the result of the development of information technology. Hindu religious instructors, as part of the community, can also use this technology in carrying out the task of giving life enlightenment to Hindus. This study reveals how Hindu religious education is carried out by Hindu religious instructors in the Abiansemal sub-district, how social media is used to support counseling activities and how the impact of the use of social media on Hindu interest in accessing Hindu religious content through social media. Internet observations and field interviews provide information about the use of social media for Hindu religious counseling, but not all instructors use it optimally. Users of social media in the Abiansemal sub-district interviewed randomly said that most people interact through social media, where the content communicated is still general, the content of Hindu teachings is very rarely communicated. Such facts can also be found through direct searches on various social media platforms such as YouTube, Instagram and WhatsApp. Keywords: Social Media, Hindu Counseling